Network Reconfiguration With Soft Open Point (SOP) To Minimize Distribution Loss - Akhilaandeswary Kumara Guru (2023)
In power system industry, distribution losses and uninterrupted supply are the important aspect, which need to be fulfilled as the energy consumption by customers going up day by day. The power losses in transmission and distribution lines has been analysed and found that the losses are mostly coming from distribution lines. A method called Network Reconfiguration has been proposed in this project to overcome the complication in distribution network. Network reconfiguration is a method where it alters the topology of distribution network switches with maintaining the distribution network constraints for some given expected objectives. This project focused on distribution network reconfiguration (DNR) using Binary Particle Swarm Optimization (BPSO). The main objective of this project is to reduce the distribution losses and improve the voltage profile of the overall system, which eventually improve the reliability of the network using Network Reconfiguration considering BPSO. This (BPSO) method will be applied in 16, 33 IEEE bus distribution network to analyse the impact of this method on distribution network. The simulation was successful and the functionality of Binary Particle Swarm Optimization in distribution system is proved with reduced power losses and improvement in voltage profile. The total power loss using Newton Raphson method is 208.46kW and with Network Reconfiguration is 138.93kW in 33-Bus Distribution Network. The significant reduction in loss is followed by the improvement of voltage profile where the lowest voltage profile for Newton Raphson method is 0.9108 and using BPSO, it has been improved to 0.9475. From the results, we can see that the objectives is being met. The outcome of this study is to be an aid for the electrical engineer who works in utility company to solve the distribution system losses and voltage profile problems using the proposed method to improve the reliability of the overall network.